2012
DOI: 10.1080/08870446.2011.574699
|View full text |Cite
|
Sign up to set email alerts
|

Family relations, mental health and adherence to nutritional guidelines in patients facing dialysis initiation

Abstract: This study investigated the effect of family relations on patients' adjustment to dialysis. The two main aims were to develop a family typology, and to explore the influence of family profile on the patient's anxiety, depression and adherence to nutritional guidelines. The sample consisted of 120 patients (mean age 63 years; 67.5% of men). They completed several measures 1, 6 and 12 months after dialysis initiation. The scales used were the Family Relationship Index and the Hospital Anxiety and Depression Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 32 publications
2
23
0
2
Order By: Relevance
“…In this review, all studies that applied the MSPSS and considered its different factors (vs a total score), found significant associations with treatment adherence. Instead, most studies measuring social support with an overall score failed to sustain these results . These findings are congruent with previous literature, pointing that individuals usually differentiate between different tangible sources of support …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this review, all studies that applied the MSPSS and considered its different factors (vs a total score), found significant associations with treatment adherence. Instead, most studies measuring social support with an overall score failed to sustain these results . These findings are congruent with previous literature, pointing that individuals usually differentiate between different tangible sources of support …”
Section: Discussionsupporting
confidence: 83%
“…Four studies (100%) reported significant associations between social support and overall treatment adherence. These studies highlighted the role of caregivers, healthcare providers, and family relationships and support . Congruent results were found by Varghese and colleagues who reported a significant association between social support and overall adherence, measured by biochemical indicators of serum phosphate and inter‐dialytic weight gain …”
Section: Introductionmentioning
confidence: 95%
“…We found that those who were capable of taking care of themselves were apt to acceptance resignation coping strategy, while those patients who were unable to do so relied more on caregivers assistance to manage their illness. Previous studies showed that supportive family relationship reduced the perception of stress and facilitated active coping and recovery of patients with chronic illnesses (Schuster, Hammitt, & Moore, 2003;Untas, Rascle, Idier, Lasseur, & Combe, 2012). Thus, support from caregivers was crucial for improving the self-management and recovery, thereby enhancing their ability to cope with disease positively (Schuster et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Validated measures show a strong association between treatment adherence, engagement with outpatient resources, and mortality outcomes . Symptoms of anxiety and depression are extremely common and linked with dialysis and dietary nonadherence behaviors . Kimmel et al showed that perception of burden of illness and poor social support correlate with treatment of nonadherence, frequent hospitalization, and mortality .…”
Section: Current Gaps In Care Around Clinical and Psychosocial Risk Fmentioning
confidence: 99%
“…Social support plays a role in self‐efficacy. Support from family and friends is associated with better fluid adherence, and higher rates of social support are associated with improved dialysis treatment adherence . Over 30% of patients on hemodialysis have poor social support based on medical outcomes study surveys .…”
Section: Current Gaps In Care Around Clinical and Psychosocial Risk Fmentioning
confidence: 99%